Prevalence of OXA-Type β-Lactamase Genes among Carbapenem-Resistant Acinetobacter baumannii Clinical Isolates in Thailand - Krit Thirapanmethee; Thayapa Srisiri-; Jantana Houngsaitong; Preecha Montakantikul; Piyatip Khuntayaporn; Mullika Traidej Chomnawang (MDPI AG, 2020)
Carbapenem-resistant Acinetobacter baumannii (CRAB) is a critical health concern for the treatment of infectious diseases. The aim of this study was to investigate the molecular epidemiology of CRAB emphasizing the presence of oxacillinase (OXA)-type β-lactamase-encoding genes, one of the most important carbapenem resistance mechanisms. In this study, a total of 183 non-repetitive CRAB isolates collected from 11 tertiary care hospitals across Thailand were investigated. As a result, the blaoxa-51-like gene, an intrinsic enzyme marker, was detected in all clinical isolates. The blaoxa-23-like gene was presented in the majority of isolates (68.31%). In contrast, the prevalence rates of blaoxa-40/24-like and blaoxa-58-like gene occurrences in CRAB isolates were only 4.92% and 1.09%, respectively. All isolates were resistant to carbapenems, with 100% resistance to imipenem, followed by meropenem (98.91%) and doripenem (94.54%). Most isolates showed high resistance rates to ciprofloxacin (97.81%), ceftazidime (96.72%), gentamicin (91.26%), and amikacin (80.87%). Interestingly, colistin was found to be a potential drug of choice due to the high susceptibility of the tested isolates to this antimicrobial (87.98%). Most CRAB isolates in Thailand were of ST2 lineage, but some belonged to ST25, ST98, ST129, ST164, ST215, ST338, and ST745. Further studies to monitor the spread of carbapenem-resistant OXA-type β-lactamase genes from A. baumannii in hospital settings are warranted.